CHALLENGES OF ECONOMIC COMPETITIVENESS AND DEBT MANAGEMENT - Arya, Charu Dutt (International Journal of Research -GRANTHAALAYAH, 2025)
The rapid expansion of global trade, the unprecedented openness of domestic markets, regional integration, and the ongoing intensity of globalization present significant challenges in maintaining a balance between revenues and expenditures. These challenges span international, regional, national, corporate, and individual levels. The coexistence of external trade deficits and internal budget deficits, along with the accumulation of high debt levels by governments, non-financial corporations, and households, highlights the need for fresh theoretical and practical approaches. In the context of the current global financial crisis, new institutions and policies are essential to ensure sustainable growth and reduce the risk of increasingly unpredictable disruptions.